USING CONCEPT MAPPING TO IMPROVE THE READING ABILITY - Candra Jaya; Mohammad Adnan Latief (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
The objective of the study is to develop the concept mapping strategy to improve the reading ability of the second semester students at College of Islamic Studies Ma’arif (STAI) Metro–Lampung. A classroom action research was conducted in twocycles each comprising planning, implementing, observing, and reflecting. Observationsheet, field notes, interview, and test were used during the observation of each cycle. Thefindings of the study revealed that the concept mapping strategy that involves the use ofconcept mapping format to be filled in based on the comprehension from a Reading text has successfully improved the Reading ability of the second semester students of the English Department at STAI Ma’arief Metro Lampung. The success is indicated by thestudents’ improvement in reading scores and in the improvement of joyful learning interaction. The students enjoyed learning reading using concept mapping and found concept mapping helpful. All the students got above the passing score 60 in Cycle 2.